Religious Symbols in Public Schools as Teachable Controversies in Religious Education - Moe, Christian (CEPS journal, 2019)
This focus issue of CEPS Journal raises two topics usually treated separately, Religious Education and the use of religious symbols in public schools. Both involve the challenge of applying liberal democratic principles of secularism and pluralism in a school setting and refract policies on religion under conditions of globalisation, modernisation and migration. I take this situation as a teachable moment and argue that it illustrates the potential of a particular kind of Religious Education, based on the scientific Study of Religion, for making sense of current debates in Europe, including the debate on religious education itself. However, this requires maintaining a spirit of free, unbiased comparative enquiry that may clash with political attempts to instrumentalise the subject as a means of integrating minority students into a value system.